Role of CoQ10 and IGFBP-1 in Obese Male Patients with Diabetic Mellitus Type II - Dina A. M. Al-Khafajy1 , Maysaa J. Majeed2 , Omar F. Al-Azzawi3 ; Ayad Ismael Khaleel4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Study the role of CoQ10 and IGFBP-1 in obese male patients with diabetic mellitus type 2. ELISA methodwas used to assay Serum CoQ10 and IGFBP-1. Blood was taken with drawn sample from 30 obese normalpatients with age range (40-60) years, 30 diabetic patients with age range (40-60) years at duration of disease(1-5) years and 30 normal healthy patients. The mean difference between T2DM according to CoQ10(12.5±1.1) was decreased than the mean of IFG (21.8±3.2) (P 0.002) and the mean difference betweenT2DM according to IGFBPs (0.65±0.06) was decreased than the mean of IFG (3.2±0.3) (P 0.000). Whileno significant difference between mean age of DM2 patients (55.5±1.06), and IFG (55.6±0.9) (p 0.90), nosignificant difference between mean BMI of DM2 patients (27.7±0.8), and IFG (27.8±0.5) (p 0.94). therewere significant differences in DM and IFG obese groups (G1 and G2) according to age (51.66 ±2.10,51.80±1.16) P (0.02), however, there were significant differences between DM and IFG in Normal weightgroups (G5 and G6) according to age (59.93±0.94, 51.13±1.80) P (0.00), while no significant differencesbetween DM and IFG in Over weight groups (G3 and G4) according to age (54.93±1.17, 58.00±1.73) p(0.21),there were significant differences between DM2 and IFG in obese groups (G1 and G2) according to BMI(33.70±1.20, 31.11±0.37) P (0.01), ), no significant difference between overweight (G3 and G4) accordingto BMI (27.72±0.30, 27.52±0.34) P(0.66), and no significant difference between normal weight (G5 and G6)according to BMI (21.84±0.45, 21.53±0.50) P(0.65). There were significant differences between DM andIFG in obese groups (G1 and G2) according to CoQ10 (7.2±0.4, 4.9±0.4) P (0.002), and IGFBP (0.3±0.02,1.2±0.19) P (0.005).